A wood-plastic composite material board with adsorption and purification function and its preparation method
Through specific raw material combination and preparation methods, the mechanical properties and air purification capabilities of plastic wood composite materials are improved, the performance shortcomings in the existing technology are solved, and the efficient and long-life air purification effect is achieved.
Patent Information
- Application Number
- CN202410557406.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-07
- Publication Date
- 2025-08-08
- Estimated Expiration
- 2044-05-07
AI Technical Summary
The existing plastic wood composite materials have insufficient anti-mold, anti-aging, wear and corrosion resistance, low bond strength, short service life, and air purification effect need to be improved.
The composite sheet is prepared by extrusion and molding, such as plant fiber powder, waste PBT resin, 2,3,5,6-tetrafluoroterephthalene dimethyl alcohol/2,6-pyridine dicarboxylic chloride/1,4-diamino-2,3-dicyanoanthraquinone polymer, glass fiber, 2-naphthalamine-3,6,8-trisulfonic acid, phosphorus pentoxide, polyphosphoric acid, coupling agent, antioxidant, lubricant, environmentally friendly plasticizer, foaming agent and porous spherical titanium dioxide.
The prepared composite sheet has excellent mechanical and mechanical properties, good heat resistance and aging resistance, significant air purification effect, long service life, environmentally friendly and efficient, and is suitable for continuous large-scale production.
Smart Images

Figure BDA0004826453970000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a wood-plastic composite material plate with adsorption and purification functions and a preparation method thereof. Background Art
[0002] Wood-plastic composites (WPCs) are an emerging, environmentally friendly, low-carbon composite material. They are primarily composed of waste plastics, plant fibers, and chemical additives, typically extruded into profiles. These composites offer excellent dimensional stability, high specific strength, repeated recycling, and environmental benefits. They are now widely used in interior and exterior construction, transportation, packaging, and decoration. As their application continues to expand, market demand for WPCs is growing, and performance requirements are also becoming increasingly demanding.
[0003] Existing wood-plastic composite materials still suffer from technical deficiencies, including suboptimal mildew resistance, aging resistance, wear resistance, and corrosion resistance, as well as a short service life, weak bonding strength between materials, and the need for further improvement in the physical and mechanical properties of the products. Furthermore, as wood-plastic materials gain increasing market acceptance, demand for specialized properties is also increasing. For example, if a wood-plastic composite material not only meets the characteristics of standard materials but also possesses an adsorption function, capable of absorbing harmful gases and dust, it would be highly beneficial for purifying indoor air and, therefore, would be even more popular.
[0004] To address the aforementioned issues, Chinese invention patent CN111572146B discloses a plastic-wood composite material board with adsorption and purification capabilities and its preparation method, belonging to the technical fields of composite materials and novel chemical building materials. The invention comprises a lignin / plastic composite core layer, a wood flour / plastic composite intermediate layer, and a chitosan-modified outer shell layer, with the wood flour / plastic composite intermediate layer positioned between the lignin / plastic composite core layer and the chitosan-modified outer shell layer. This invention offers ease of manufacture, strong production continuity, and high production efficiency. Compared to wood materials, it is more resistant to corrosion and insect infestation, resists cracking, aging, color shift, and paint loss during use. Compared to conventional plastic-wood composites, its porous structure and the use of materials with adsorbent properties result in excellent adsorption of toxic and harmful gases and dust, contributing to air purification, particularly indoor air, and improving the living environment. However, the material's performance stability and heat aging resistance still need to be further improved, as does its formaldehyde purification effectiveness.
[0005] It can be seen that the development of a plastic-wood composite material board with adsorption and purification functions that has good mechanical properties, good heat aging resistance, significant air purification effect, and long service life and its preparation method meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the plastic-wood composite material field. Summary of the Invention
[0006] In view of the above problems, the object of the present invention is to provide a plastic-wood composite material board with adsorption and purification functions, which has good mechanical properties, good heat aging resistance, significant air purification effect, and long service life, and a preparation method thereof.
[0007] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a plastic-wood composite material board with adsorption and purification functions is made of the following raw materials in parts by weight: 30-40 parts of plant fiber powder, 60-70 parts of waste PBT resin, 6-12 parts of 2,3,5,6-tetrafluorophenylenedimethanol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer, 3-5 parts of glass fiber, 3-5 parts of 2-naphthylamine-3,6,8-trisulfonic acid, 0.8-1.5 parts of phosphorus pentoxide, 0.3-0.5 parts of polyphosphoric acid, 1-3 parts of coupling agent, 0.7-1 parts of antioxidant, 1-2 parts of lubricant, 3-5 parts of environmentally friendly plasticizer, 1-3 parts of foaming agent, and 8-10 parts of porous spherical titanium dioxide.
[0008] Preferably, there is no special requirement for the source of the porous spherical titanium dioxide. In one embodiment of the present invention, the porous spherical titanium dioxide is prepared according to the method of Example 1 of the Chinese invention patent with authorization publication number CN104587995B.
[0009] Preferably, the foaming agent is medium-temperature foaming agent HH808B, provided by Hangzhou Lingebei Technology Co., Ltd.
[0010] Preferably, the environmentally friendly plasticizer is epoxidized soybean oil.
[0011] Preferably, the lubricant is at least one of pentaerythritol stearate and ethylene bisstearamide.
[0012] Preferably, the antioxidant is at least one of antioxidant 1010, antioxidant 1076, and antioxidant 168.
[0013] Preferably, the coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570.
[0014] Preferably, the glass fiber is alkali-free chopped glass fiber, with a single fiber diameter of 3-9 μm and a length of 1-3 mm.
[0015] Preferably, the preparation method of the 2,3,5,6-tetrafluorophenylenedimethanol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer comprises the following steps: dispersing 2,3,5,6-tetrafluorophenylenedimethanol, 2,6-pyridinedicarbonyl chloride, 1,4-diamino-2,3-dicyanoanthraquinone, and an alkaline catalyst in a solvent, stirring and reacting in an ice-water bath under an inert gas atmosphere for 3-5 hours, then stirring and reacting at room temperature for 6-8 hours. After the reaction is completed, the mixture is precipitated in water, and the precipitated polymer is washed with ethanol 3-6 times, and finally dried in a vacuum drying oven at 85-95° C. to constant weight to obtain a 2,3,5,6-tetrafluorophenylenedimethanol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer.
[0016] Preferably, the molar ratio of the 2,3,5,6-tetrafluorophenylenedimethanol, 2,6-pyridinedicarbonyl chloride, 1,4-diamino-2,3-dicyanoanthraquinone, alkaline catalyst, and solvent is 0.7:1:0.3:(2-3):(15-25).
[0017] Preferably, the alkaline catalyst is at least one of triethylamine and pyridine.
[0018] Preferably, the solvent is dichloromethane.
[0019] Preferably, the inert gas is any one of nitrogen, helium, neon and argon.
[0020] Preferably, the waste PBT resin is recycled American Ticona 1700A high molecular weight PBT Celanex resin waste.
[0021] Preferably, the plant fiber powder is at least one of wood fiber powder, hemp fiber powder, bamboo fiber powder, grass fiber powder, bran powder or straw fiber powder; and the particle size of the plant fiber powder is 100-300 mesh.
[0022] Another object of the present invention is to provide a method for preparing the plastic-wood composite material board with adsorption and purification functions, comprising the following steps: drying the plant fiber powder at 95-115°C for 2-4 hours, then mixing it evenly with other raw materials, adding it to an extruder for extrusion, and obtaining the plastic-wood composite material board with adsorption and purification functions after molding.
[0023] Preferably, the temperature of the extruder is 230-260° C., and the head pressure of the extruder is 10-15 MPa.
[0024] Preferably, the compression molding pressure is 18-22 MPa, and the time is 12-15 min.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The method for preparing the wood-plastic composite material board with adsorption and purification functions disclosed in the present invention can be realized by conventional operations, has low labor intensity, low dependence on equipment, high preparation efficiency and finished product qualification rate, is suitable for continuous large-scale production, and realizes the organic unity of economic benefits, social benefits and ecological benefits.
[0027] (2) The plastic-wood composite material board with adsorption and purification functions disclosed in the present invention is made of the following raw materials in parts by weight: 30-40 parts of plant fiber powder, 60-70 parts of waste PBT resin, 6-12 parts of 2,3,5,6-tetrafluorophenylenedimethanol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer, 3-5 parts of glass fiber, 3-5 parts of 2-naphthylamine-3,6,8-trisulfonic acid, 0.8-1.5 parts of phosphorus pentoxide, 0.3-0.5 parts of polyphosphoric acid, 1-3 parts of coupling agent, 0.7-1 parts of antioxidant, 1-2 parts of lubricant, 3-5 parts of environmentally friendly plasticizer, 1-3 parts of foaming agent, and 8-10 parts of porous spherical titanium dioxide. Through the mutual cooperation between the raw materials, the composite material board has good mechanical properties, good heat aging resistance, significant air purification effect, and long service life.
[0028] (3) The plastic-wood composite material board with adsorption and purification functions disclosed in the present invention uses plant fiber powder and waste PBT resin as its base material, realizing the transformation of waste into treasure. This not only saves resources but also contributes to environmental protection, reduces product production costs, and improves economic, social, and ecological benefits. Tetrafluorobenzene, ester, amide, cyanoanthraquinone, and pyridine structures are simultaneously introduced into the 2,3,5,6-tetrafluorophenylenedimethanol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer. These structures, under the multiple effects of electronic effects, steric effects, and conjugated effects, make the resulting composite material board have better mechanical properties, better heat aging resistance, and longer service life.
[0029] (4) In the wood-plastic composite material board with adsorption and purification functions disclosed in the present invention, the sulfonic acid group on 2-naphthylamine-3,6,8-trisulfonic acid can chemically react with the benzene ring on other benzene ring-containing raw materials to form an interpenetrating network structure, thereby effectively improving the comprehensive performance and performance stability of the composite material board; the porous spherical titanium dioxide with adsorption and photocatalytic functions is fixed in the network structure, so that the manufactured board has better mechanical properties, better heat aging resistance, more significant air purification effect, and longer service life. DETAILED DESCRIPTION
[0030] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below with reference to embodiments.
[0031] Example 1
[0032] A plastic-wood composite material board with adsorption and purification functions is made of the following raw materials in parts by weight: 30 parts of plant fiber powder, 60 parts of waste PBT resin, 6 parts of 2,3,5,6-tetrafluorophenylenediol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer, 3 parts of glass fiber, 3 parts of 2-naphthylamine-3,6,8-trisulfonic acid, 0.8 parts of phosphorus pentoxide, 0.3 parts of polyphosphoric acid, 1 part of coupling agent, 0.7 parts of antioxidant, 1 part of lubricant, 3 parts of environmentally friendly plasticizer, 1 part of foaming agent, and 8 parts of porous spherical titanium dioxide.
[0033] The porous spherical titanium dioxide is made according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN104587995B; the foaming agent is the medium-temperature foaming agent HH808B, provided by Hangzhou Lingbei Technology Co., Ltd.; the environmentally friendly plasticizer is epoxidized soybean oil; the lubricant is pentaerythritol stearate; the antioxidant is antioxidant 1010; the coupling agent is silane coupling agent KH550; the glass fiber is alkali-free chopped glass fiber, with a single filament diameter of 3 μm and a length of 1 mm.
[0034] The preparation method of the 2,3,5,6-tetrafluorophenylenedimethanol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer comprises the following steps: dispersing 2,3,5,6-tetrafluorophenylenedimethanol, 2,6-pyridinedicarbonyl chloride, 1,4-diamino-2,3-dicyanoanthraquinone, and an alkaline catalyst in a solvent, stirring and reacting in an ice-water bath under an inert gas atmosphere for 3 hours, and then stirring and reacting at room temperature for 6 hours. After the reaction is completed, the polymer is precipitated in water, and the precipitated polymer is washed with ethanol. 3 times, and finally placed in a vacuum drying oven at 85 ° C to dry to constant weight, to obtain a 2,3,5,6-tetrafluorophenylenedimethanol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer; the molar ratio of the 2,3,5,6-tetrafluorophenylenedimethanol, 2,6-pyridinedicarbonyl chloride, 1,4-diamino-2,3-dicyanoanthraquinone, alkaline catalyst, and solvent is 0.7:1:0.3:2:15; the alkaline catalyst is triethylamine; the solvent is dichloromethane; and the inert gas is nitrogen. The M of the obtained polymer was measured by GPC test. n =16113 g / mol, M W / M n=1.326; calculated by elemental analysis and weight change, the molar ratio of the structural units introduced by 2,3,5,6-tetrafluorophenylenedimethanol, 2,6-pyridinedicarbonyl chloride, and 1,4-diamino-2,3-dicyanoanthraquinone in the triazolylbiphenyl functional polymer is approximately 0.7:1:0.3, which is the same as the theoretical value.
[0035] The waste PBT resin is recycled American Ticona 1700A high molecular weight PBT Celanex resin waste; the plant fiber powder is wood fiber powder; and the particle size of the plant fiber powder is 100 mesh.
[0036] A method for preparing the plastic-wood composite material board with adsorption and purification functions comprises the following steps: drying plant fiber powder at 95°C for 2 hours, then uniformly mixing it with other raw materials, adding it to an extruder for extrusion, and compression molding to obtain the plastic-wood composite material board with adsorption and purification functions; the temperature of the extruder is 230°C, the head pressure of the extruder is 10MPa; the compression molding pressure is 18MPa, and the time is 12 minutes.
[0037] Example 2
[0038] A plastic-wood composite material board with adsorption and purification functions is made from the following raw materials in parts by weight: 33 parts of plant fiber powder, 62 parts of waste PBT resin, 8 parts of 2,3,5,6-tetrafluorophenylenediol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer, 3.5 parts of glass fiber, 3.5 parts of 2-naphthylamine-3,6,8-trisulfonic acid, 1 part of phosphorus pentoxide, 0.35 part of polyphosphoric acid, 1.5 parts of coupling agent, 0.8 part of antioxidant, 1.2 parts of lubricant, 3.5 parts of environmentally friendly plasticizer, 1.5 parts of foaming agent, and 8.5 parts of porous spherical titanium dioxide.
[0039] The porous spherical titanium dioxide is made according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN104587995B; the foaming agent is the medium-temperature foaming agent HH808B, provided by Hangzhou Lingbei Technology Co., Ltd.; the environmentally friendly plasticizer is epoxy soybean oil; the lubricant is ethylene bisstearamide; the antioxidant is antioxidant 1076; the coupling agent is silane coupling agent KH560; the glass fiber is alkali-free chopped glass fiber, with a single filament diameter of 5 μm and a length of 1.5 mm.
[0040] The preparation method of the 2,3,5,6-tetrafluorophenylenedimethanol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer comprises the following steps: dispersing 2,3,5,6-tetrafluorophenylenedimethanol, 2,6-pyridinedicarbonyl chloride, 1,4-diamino-2,3-dicyanoanthraquinone and an alkaline catalyst in a solvent, stirring and reacting in an ice-water bath under an inert gas atmosphere for 3.5 hours, then stirring and reacting at room temperature for 6.5 hours, and after the reaction is completed, precipitating the polymer in water, and rinsing the precipitated polymer with ethanol. The mixture was washed four times and finally dried in a vacuum drying oven at 87° C. to constant weight to obtain a 2,3,5,6-tetrafluorophenylenedimethanol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer; the molar ratio of the 2,3,5,6-tetrafluorophenylenedimethanol, 2,6-pyridinedicarbonyl chloride, 1,4-diamino-2,3-dicyanoanthraquinone, alkaline catalyst, and solvent was 0.7:1:0.3:2.3:17; the alkaline catalyst was pyridine; the solvent was dichloromethane; and the inert gas was helium.
[0041] The waste PBT resin is recycled American Ticona 1700A high molecular weight PBT Celanex resin waste; the plant fiber powder is hemp fiber powder; and the particle size of the plant fiber powder is 150 mesh.
[0042] A method for preparing the wood-plastic composite material board with adsorption and purification functions comprises the following steps: drying plant fiber powder at 100°C for 2.5 hours, then uniformly mixing the plant fiber powder with other raw materials, adding the powder to an extruder for extrusion, and compression molding the resulting wood-plastic composite material board with adsorption and purification functions; the temperature of the extruder is 240°C, the head pressure of the extruder is 11 MPa; the compression molding pressure is 19 MPa, and the time is 13 minutes.
[0043] Example 3
[0044] A plastic-wood composite material board with adsorption and purification functions is made from the following raw materials, measured in parts by weight: 35 parts of plant fiber powder, 65 parts of waste PBT resin, 9 parts of 2,3,5,6-tetrafluorophenylenediol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer, 4 parts of glass fiber, 4 parts of 2-naphthylamine-3,6,8-trisulfonic acid, 1.3 parts of phosphorus pentoxide, 0.4 parts of polyphosphoric acid, 2 parts of coupling agent, 0.85 parts of antioxidant, 1.5 parts of lubricant, 4 parts of environmentally friendly plasticizer, 2 parts of foaming agent, and 9 parts of porous spherical titanium dioxide.
[0045] The porous spherical titanium dioxide is made according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN104587995B; the foaming agent is the medium-temperature foaming agent HH808B, provided by Hangzhou Lingbei Technology Co., Ltd.; the environmentally friendly plasticizer is epoxy soybean oil; the lubricant is pentaerythritol stearate; the antioxidant is antioxidant 168; the coupling agent is silane coupling agent KH570; the glass fiber is alkali-free chopped glass fiber, with a single filament diameter of 6 μm and a length of 2 mm.
[0046] The preparation method of the 2,3,5,6-tetrafluorophenylenedimethanol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer comprises the following steps: dispersing 2,3,5,6-tetrafluorophenylenedimethanol, 2,6-pyridinedicarbonyl chloride, 1,4-diamino-2,3-dicyanoanthraquinone, and an alkaline catalyst in a solvent, stirring and reacting in an ice-water bath in an inert gas atmosphere for 4 hours, then stirring and reacting at room temperature for 7 hours, and after the reaction is completed, precipitating the polymer in water, and washing the precipitated polymer with ethanol for 5 minutes. times, and finally dried in a vacuum drying oven at 90° C. to constant weight to obtain a 2,3,5,6-tetrafluorophenylenedimethanol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer; the molar ratio of the 2,3,5,6-tetrafluorophenylenedimethanol, 2,6-pyridinedicarbonyl chloride, 1,4-diamino-2,3-dicyanoanthraquinone, alkaline catalyst, and solvent is 0.7:1:0.3:2.5:20; the alkaline catalyst is triethylamine; the solvent is dichloromethane; and the inert gas is neon.
[0047] The waste PBT resin is recycled American Ticona 1700A high molecular weight PBT Celanex resin waste; the plant fiber powder is bamboo fiber powder; and the particle size of the plant fiber powder is 200 meshes.
[0048] A method for preparing the plastic-wood composite material board with adsorption and purification functions comprises the following steps: drying plant fiber powder at 105°C for 3 hours, then uniformly mixing the plant fiber powder with other raw materials, adding the powder to an extruder for extrusion, and compression molding the resulting plastic-wood composite material board with adsorption and purification functions; the temperature of the extruder is 245°C, the head pressure of the extruder is 13 MPa; the compression molding pressure is 20 MPa, and the time is 13.5 minutes.
[0049] Example 4
[0050] A plastic-wood composite material board with adsorption and purification functions is made from the following raw materials, measured in parts by weight: 38 parts of plant fiber powder, 68 parts of waste PBT resin, 11 parts of 2,3,5,6-tetrafluorophenylenediol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer, 4.5 parts of glass fiber, 4.5 parts of 2-naphthylamine-3,6,8-trisulfonic acid, 1.3 parts of phosphorus pentoxide, 0.45 parts of polyphosphoric acid, 2.5 parts of coupling agent, 0.9 part of antioxidant, 1.8 parts of lubricant, 4.5 parts of environmentally friendly plasticizer, 2.5 parts of foaming agent, and 9.5 parts of porous spherical titanium dioxide.
[0051] The porous spherical titanium dioxide is made according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN104587995B; the foaming agent is a medium-temperature foaming agent HH808B, provided by Hangzhou Lingbei Technology Co., Ltd.; the environmentally friendly plasticizer is epoxidized soybean oil; the lubricant is a mixture of pentaerythritol stearate and ethylene bisstearamide in a mass ratio of 1:3; the antioxidant is a mixture of antioxidant 1010, antioxidant 1076, and antioxidant 168 in a mass ratio of 1:2:2; the coupling agent is a mixture of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570 in a mass ratio of 2:1:3; the glass fiber is an alkali-free chopped glass fiber with a single fiber diameter of 8 μm and a length of 2.5 mm.
[0052] The preparation method of the 2,3,5,6-tetrafluorophenylenedimethanol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer comprises the following steps: dispersing 2,3,5,6-tetrafluorophenylenedimethanol, 2,6-pyridinedicarbonyl chloride, 1,4-diamino-2,3-dicyanoanthraquinone and an alkaline catalyst in a solvent, stirring and reacting in an ice-water bath under an inert gas atmosphere for 4.5 hours, then stirring and reacting at room temperature for 7.5 hours, and after the reaction is completed, precipitating the polymer in water, washing the precipitated polymer with ethanol for 6 times, and finally placing the polymer in a vacuum evaporator. The product was dried in an empty drying oven at 93° C. to constant weight to obtain a 2,3,5,6-tetrafluorophenylenedimethanol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer; the molar ratio of the 2,3,5,6-tetrafluorophenylenedimethanol, 2,6-pyridinedicarbonyl chloride, 1,4-diamino-2,3-dicyanoanthraquinone, alkaline catalyst, and solvent was 0.7:1:0.3:2.8:23; the alkaline catalyst was a mixture of triethylamine and pyridine in a mass ratio of 3:5; the solvent was dichloromethane; and the inert gas was argon.
[0053] The waste PBT resin is recycled American Ticona 1700A high molecular weight PBT Celanex resin waste; the plant fiber powder is a mixture of wood fiber powder, hemp fiber powder, bamboo fiber powder, grass fiber powder, bran powder, and straw fiber powder in a mass ratio of 1:2:3:1:1:2; the particle size of the plant fiber powder is 250 mesh.
[0054] A method for preparing the plastic-wood composite material board with adsorption and purification functions comprises the following steps: drying plant fiber powder at 112° C. for 3.5 hours, then uniformly mixing the plant fiber powder with other raw materials, adding the powder to an extruder for extrusion, and compression molding the resulting plastic-wood composite material board with adsorption and purification functions; the temperature of the extruder is 255° C., the head pressure of the extruder is 14 MPa; the compression molding pressure is 21 MPa, and the time is 14.5 minutes.
[0055] Example 5
[0056] A plastic-wood composite material board with adsorption and purification functions is made of the following raw materials, measured in parts by weight: 40 parts of plant fiber powder, 70 parts of waste PBT resin, 12 parts of 2,3,5,6-tetrafluorophenylenediol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer, 5 parts of glass fiber, 5 parts of 2-naphthylamine-3,6,8-trisulfonic acid, 1.5 parts of phosphorus pentoxide, 0.5 part of polyphosphoric acid, 3 parts of coupling agent, 1 part of antioxidant, 2 parts of lubricant, 5 parts of environmentally friendly plasticizer, 3 parts of foaming agent, and 10 parts of porous spherical titanium dioxide.
[0057] The porous spherical titanium dioxide is made according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN104587995B; the foaming agent is the medium-temperature foaming agent HH808B, provided by Hangzhou Lingbei Technology Co., Ltd.; the environmentally friendly plasticizer is epoxy soybean oil; the lubricant is pentaerythritol stearate; the antioxidant is antioxidant 1076; the coupling agent is silane coupling agent KH570; the glass fiber is alkali-free chopped glass fiber, with a single filament diameter of 9 μm and a length of 3 mm.
[0058] The preparation method of the 2,3,5,6-tetrafluorophenylenedimethanol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer comprises the following steps: dispersing 2,3,5,6-tetrafluorophenylenedimethanol, 2,6-pyridinedicarbonyl chloride, 1,4-diamino-2,3-dicyanoanthraquinone, and an alkaline catalyst in a solvent, stirring and reacting in an ice-water bath under an inert gas atmosphere for 5 hours, and then stirring and reacting at room temperature for 8 hours. After the reaction is completed, the polymer is precipitated in water, and the precipitated polymer is washed with ethanol. The product was washed 6 times and finally dried in a vacuum drying oven at 95° C. to constant weight to obtain a 2,3,5,6-tetrafluorophenylenedimethanol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer; the molar ratio of the 2,3,5,6-tetrafluorophenylenedimethanol, 2,6-pyridinedicarbonyl chloride, 1,4-diamino-2,3-dicyanoanthraquinone, alkaline catalyst, and solvent was 0.7:1:0.3:3:25; the alkaline catalyst was pyridine; the solvent was dichloromethane; and the inert gas was nitrogen.
[0059] The waste PBT resin is recycled American Ticona 1700A high molecular weight PBT Celanex resin waste; the plant fiber powder is straw fiber powder; and the particle size of the plant fiber powder is 300 meshes.
[0060] A method for preparing the plastic-wood composite material board with adsorption and purification functions comprises the following steps: drying plant fiber powder at 115°C for 4 hours, then uniformly mixing the plant fiber powder with other raw materials, adding the powder to an extruder for extrusion, and compression molding the plant fiber powder to obtain the plastic-wood composite material board with adsorption and purification functions; the temperature of the extruder is 260°C, the head pressure of the extruder is 15 MPa; the compression molding pressure is 22 MPa, and the time is 15 minutes.
[0061] Comparative Example 1
[0062] A plastic-wood composite material plate with adsorption and purification functions and a preparation method thereof are basically the same as those in Example 1, except that 2,3,5,6-tetrafluorophenylenedimethanol is used instead of 1,4-diamino-2,3-dicyanoanthraquinone.
[0063] Comparative Example 2
[0064] A wood-plastic composite material plate with adsorption and purification functions and a preparation method thereof are basically the same as those in Example 1, except that 1,4-diamino-2,3-dicyanoanthraquinone is used instead of 2,3,5,6-tetrafluorophenylenedimethanol.
[0065] In order to further illustrate the unexpected positive technical effects achieved by the products of each embodiment of the present invention, relevant performance tests were conducted on the plastic-wood composite material boards with adsorption and purification functions prepared in each example. The test results are shown in Table 1. The test method is as follows:
[0066] (1) Static flexure strength: The static flexure strength of the present invention was tested according to LY / T 1613 standard;
[0067] (2) Heat aging resistance: Each example of plastic-wood composite material board product with adsorption and purification function was placed in hot air at 85°C for artificial accelerated aging for 168 hours. After cooling to room temperature, the static bending strength was measured again. The heat aging resistance was measured by the retention rate of the static bending strength. The larger the value, the better the heat aging resistance.
[0068] (3) Formaldehyde purification performance and durability of formaldehyde purification effect: Tested according to the method in JC / T1074-2008.
[0069] Table 1
[0070]
[0071] As shown in Table 1, the wood-plastic composite material with adsorption and purification functions disclosed in the examples of the present invention exhibits superior air purification performance, better mechanical properties, and heat aging resistance compared to the comparative examples. The combined use of 2,3,5,6-tetrafluorophenylenedimethanol and 1,4-diamino-2,3-dicyanoanthraquinone is beneficial in improving these properties.
[0072] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any ordinary technician in this industry can smoothly implement the present invention as described above. However, any equivalent changes, modifications and evolutions made by technicians familiar with this profession without departing from the scope of the technical solution of the present invention using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the scope of protection of the technical solution of the present invention.
Claims
1. A wood-plastic composite material board with adsorption and purification functions, characterized in that: The invention is prepared from the following raw materials in parts by weight: 30-40 parts of plant fiber powder, 60-70 parts of waste PBT resin, 6-12 parts of 2,3,5,6-tetrafluorophenylenediol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer, 3-5 parts of glass fiber, 3-5 parts of 2-naphthylamine-3,6,8-trisulfonic acid, 0.8-1.5 parts of phosphorus pentoxide, 0.3-0.5 parts of polyphosphoric acid, 1-3 parts of coupling agent, 0.7-1 parts of antioxidant, 1-2 parts of lubricant, 3-5 parts of environmentally friendly plasticizer, 1-3 parts of foaming agent, and 8-10 parts of porous spherical titanium dioxide. The preparation method of the 2,3,5,6-tetrafluorophenylenedimethanol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer comprises the following steps: dispersing 2,3,5,6-tetrafluorophenylenedimethanol, 2,6-pyridinedicarbonyl chloride, 1,4-diamino-2,3-dicyanoanthraquinone and an alkaline catalyst in a solvent, stirring and reacting in an ice-water bath under an inert gas atmosphere for 3-5 hours, then stirring and reacting at room temperature for 6-8 hours, and after the reaction is completed, precipitating in water and The precipitated polymer is washed with ethanol 3-6 times and finally dried in a vacuum drying oven at 85-95° C. to constant weight to obtain a 2,3,5,6-tetrafluorophenylenedimethanol / 2,6-pyridinedicarbonyl chloride / 1,4-diamino-2,3-dicyanoanthraquinone polymer; the molar ratio of the 2,3,5,6-tetrafluorophenylenedimethanol, 2,6-pyridinedicarbonyl chloride, 1,4-diamino-2,3-dicyanoanthraquinone, alkaline catalyst, and solvent is 0.7:1:0.3:(2-3):(15-25).
2. The wood-plastic composite material board with adsorption and purification function according to claim 1, characterized in that: The foaming agent is medium-temperature foaming agent HH808B; the environmentally friendly plasticizer is epoxidized soybean oil.
3. The wood-plastic composite material board with adsorption and purification function according to claim 1, characterized in that: The lubricant is at least one of pentaerythritol stearate and ethylene bisstearamide; the antioxidant is at least one of antioxidant 1010, antioxidant 1076, and antioxidant 168.
4. The wood-plastic composite material board with adsorption and purification function according to claim 1, characterized in that: The coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570; the glass fiber is alkali-free chopped glass fiber, with a single fiber diameter of 3-9 μm and a length of 1-3 mm.
5. The wood-plastic composite material board with adsorption and purification function according to claim 1, characterized in that: The alkaline catalyst is at least one of triethylamine and pyridine; the solvent is dichloromethane; and the inert gas is any one of nitrogen, helium, neon, and argon.
6. The wood-plastic composite material board with adsorption and purification function according to claim 1, characterized in that: The waste PBT resin is recycled American Ticona 1700A high molecular weight PBT Celanex resin waste; the plant fiber powder is at least one of wood fiber powder, hemp fiber powder, bamboo fiber powder, grass fiber powder, bran powder or straw fiber powder; the particle size of the plant fiber powder is 100-300 mesh.
7. A method for preparing a wood-plastic composite material board with adsorption and purification functions according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: drying plant fiber powder at 95-115° C. for 2-4 hours, then uniformly mixing the plant fiber powder with other raw materials, adding the powder into an extruder for extrusion, and molding the powder to obtain a plastic-wood composite material plate with adsorption and purification functions.
8. The method for preparing a wood-plastic composite material board with adsorption and purification functions according to claim 7, characterized in that: The temperature of the extruder is 230-260° C., and the head pressure of the extruder is 10-15 MPa; the pressure of the compression molding is 18-22 MPa, and the time is 12-15 minutes.
Citation Information
Patent Citations
A method for preparing porous spherical titanium dioxide
CN104587995B
A wood-plastic composite board with adsorption and purification function and its preparation method
CN111572146B
Montmorillonite reinforced wood-plastic plate for experiment table and preparation method thereof
CN106336679A
Environment-friendly PBT (Polybutylene Terephthalate) decoration membrane and adhesive tape produced by applying membrane
CN108676511A